2020
DOI: 10.1101/2020.08.12.20173526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient outcomes after hospitalisation with COVID-19 and implications for follow-up; results from a prospective UK cohort

Abstract: Background: COVID19 causes a wide spectrum of disease. However, the incidence and severity of sequelae after the acute infection is uncertain. Data measuring the longer-term impact of COVID19 on symptoms, radiology and pulmonary function are urgently needed to inform patients and plan follow up services. Methods: Consecutive patients hospitalised with COVID19 were prospectively recruited to an observational cohort with outcomes recorded at 28 days. All were invited to a systematic follow up at 12 weeks, inclu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
243
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(269 citation statements)
references
References 18 publications
11
243
2
11
Order By: Relevance
“…To date, there has been little research looking for factors that predispose to long-term COVID-19 symptoms. Our finding that the initial severity of the illness is correlated with long-term outcomes is in line with the higher rates of long-term symptoms found in previous studies of hospitalized patients and a previous observation that more severely ill hospitalized patients have more long-term symptoms 6,7 . Our study was underpowered to identify other factors predisposing to long-term symptoms, though we do identify a significant association between the initial symptom of dyspnea and symptoms lasting longer than 30 days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To date, there has been little research looking for factors that predispose to long-term COVID-19 symptoms. Our finding that the initial severity of the illness is correlated with long-term outcomes is in line with the higher rates of long-term symptoms found in previous studies of hospitalized patients and a previous observation that more severely ill hospitalized patients have more long-term symptoms 6,7 . Our study was underpowered to identify other factors predisposing to long-term symptoms, though we do identify a significant association between the initial symptom of dyspnea and symptoms lasting longer than 30 days.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of long-term symptoms from COVID-19 have typically focused on distinct subsets of COVID-19 patients and in particular have not included mild cases or population controls 6,12,13 . Previous studies of hospitalized COVID-19 patients found that 74-88% of COVID-19 patients who have severe initial illness still have symptoms after 50-80 days 6,7 . Another patient-led study found that >80% of those who self-recruit into a COVID-19 study on long-term symptoms still have symptoms after 50 days 12 .…”
Section: Discussionmentioning
confidence: 95%
“…As prevention efforts have focused on minimizing mortality, the morbidity of COVID-19 illness has been underappreciated. Recent studies show that a growing number of patients with COVID-19 will experience prolonged symptoms, the profile and timeline of which remains uncertain [2][3][4][5][6]. Early in the course of the pandemic, patients identified this trend, referring to themselves as "Long-Haulers" and the prolonged illness as "Long COVID" [7].…”
Section: Introductionmentioning
confidence: 99%
“…6 Nor is it apparent to what extent cardiorespiratory pathophysiology explains the persistent fatigue, dyspnoea, or chest pain in up to 74% of patients 2-3 months postadmission. 1,10 Large population based multiorgan studies are underway to address these questions. Perhaps we should be reassured that most of the patients in the CMR studies had normal ventricular function, N-terminal pro B-type natriuretic peptide (NT-proBNP) levels, and cardiac troponin levels at the time of the scan.…”
Section: Post-acute and Chronic Cardiac Injurymentioning
confidence: 99%